Genetic Improvement And Cytogenetical Studies In Thamaravenda [Abelmoschus Manihot (L.)] - Reena Susan Chacko (Department Of Olericulture, College Of Horticulture, 1996)
The present investigation on “Genetic improvement and Cytogenetical studies in Thamaravenda (A. manihot L.)” was conducted at the Vegetable research Farm, Department of Olericulture, College of Horticulture, Vellanikkara during the year 1993 – 95. The major objectives were to collect maximum number of genotypes of the local Thamaravenda type, to assess their variability, identify promising genotype among them, confirm chromosome number of the species and its species affinity with A. esculentus and the “Thamaravenda” type, AM – 4. Twenty two genotypes of Thamaravenda collected from different parts of Kerala were raised in randomized block design in the field and statistical analysis was done on the various observations recorded namely plant height, number of primary branches, main stem diameter, number of internodes on mainstem, internodal length, fruit length, fruit girth, single fruit weight, fruits per plant, yield per plant, seeds per fruit and hundred seed weight. The genotypes expressed significant variation for all the characters studied. Genotype AM – 27 showed a combination of desirable characters like highest number of fruits per plant, high yield and long fruits. High value of genotypic coefficient of variation combined with high heritability was shown by characters like fruits per plant, yield per plant, number of fruit ridges and height of plant. Fruit length and fruits per plant showed significant positive correlation with yield. Fruits per plant showed the highest positive direct effect on yield. Using Euclinear cluster analysis the 22 genotypes were grouped in to three clusters each having fifteen, one and six genotypes respectively. The solitary cluster 11 consisted of AM – 27. The chromosome number of A. esculentus line AE – 202 and Thamaravenda type AM – 4 was confirmed to be 2n = 130 and 2n = 184 respectively. These observations indicated that AE – 202 belonged to teraploid group of A. esculentus and that AM – 4 actually came under A. caillei. In the interspecific hybrid between AE – 202 and AM – 4 all the haplophase chromosomes (n = 65) of A. esculentus were found to pair with the homeologous counter parts of AM – 4 forming 65 bivalents and 27 univalents showing a good amount of chromosome affinity between the species. The interspecific hybrids was found to be partially sterile. The synthetic amphiploid produced from the interspecific hybrid showed a lower frequency of multivalents and its chromosome number was 2n = 314 and was more fertile than F1 hybrid. The A. esculentus lines AE – 202 and Thamaravenda line AM – 4 were crossable only when AM – 4 was used as female parent.